Recruit conservation warden field training: A qualitative analysis of the San Jose Police Department Field Training Model applied to natural resource law enforcement - Groppi, Matthew (International journal of police science & management, 2021)
This article reviews the President’s Task Force on 21st Century Policing (hereafter President’s Task Force) findings on law enforcement field training. The President’s Task Force was critical of the San Jose Police Department Field Training Model (hereafter the San Jose Model), the most common model used by law enforcement agencies within the United States. These criticisms were the impetus for an assessment of the Wisconsin Department of Natural Resources (WDNR) Law Enforcement Field Training Program which was based on the San Jose Model. The WDNR employs conservation wardens who primarily enforce wildlife, environmental, and recreational vehicle laws. This study evaluates the strengths and weaknesses of the WDNR field training program through surveys of the perceptions and experiences of the field training officers, recruit conservation wardens, and warden supervisors. These findings also permit analysis regarding the criticisms identified by the President’s Task Force. The author found very little existing research pertaining to field training programs and little existing research on conservation law enforcement. The findings of this study persuaded command staff within the WDNR to follow the recommendations of the President’s Task Force and adopt the Police Training Officer (PTO) Model because it incorporated adult learning concepts, problem-based learning, and was more focused on community policing. Practical applications for other agencies are discussed and needs for future empirical research related to law enforcement field training are identified.